Expression of CK19 in papillary thyroid carcinoma in comparison with benign thyroid lesions - Abbas Fadhel , Thura (Diyala Journal of Medicine, 2023)
Background: The Papillary variant of thyroid carcinoma is one of the common types of thyroid malignancies , the commonest. Its diagnosis usually is microscopic which based on nuclear features. Objective: To assess the immunohistochemical expression of cytokeratin 19 (CK19) in PTC and compare its reactivity with other thyroid conditions to approve its importance as a useful test for diagnosing PTC. Patients and Methods: Twenty- cases of papillary thyroid carcinoma (with different variants), five follicular adenomas and ten multinodular goiters (MNG) were collected over three years (2018-2021).10% formalin-fixed sections were collected from thyroidectomy specimens. Stained with Hematoxylin and eosin then immunohistochemical staining for immune-marker CK 19 was done using standard techniques. The results were quantitatively scored as the following: score 0 (negative ), score 1+ (<5%) positive cells), score 2+ (5- 25%), score 3+ (25-75%) ,finally score 4+ (>75%) positive cells), and then calculated. Results: An 18 (90%) papillary carcinomas show diffuse and strong (3+ and 4+) expression of CK19 . ,three out of ten (30%) MNG were weakly positive(1+ and 2+) and focal in distribution while in follicular adenoma all cases were negative for CK19 . Conclusion: Ck 19 can stain benign and malignant thyroid tissue, but strong membranous staining applied in cases of papillary ca , thus can be used as confirmatorytool for PTC diagnosis.